2012
DOI: 10.1371/journal.pone.0034667
|View full text |Cite
|
Sign up to set email alerts
|

Populations of a Susceptible Amphibian Species Can Grow despite the Presence of a Pathogenic Chytrid Fungus

Abstract: Disease can be an important driver of host population dynamics and epizootics can cause severe host population declines. Batrachochytrium dendrobatidis (Bd), the pathogen causing amphibian chytridiomycosis, may occur epizootically or enzootically and can harm amphibian populations in many ways. While effects of Bd epizootics are well documented, the effects of enzootic Bd have rarely been described. We used a state-space model that accounts for observation error to test whether population trends of a species h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…By contrast, infected populations were even able to increase despite the presence of the fungus. Thus, our observation in the yellowbellied toad population Baumbach marl pit/Hergerhausen stone pit with high prevalence of Bd but population growth confirms that of Tobler et al (2012), who also concluded that observed negative effects of Bd on survival of individuals do not necessarily translate into negative effects at the population level. In yet another study, Canestrelli et al (2013) showed that Bd has been present in Apennine yellow-bellied toad populations Bombina pachypus at least since the late 1970s, but strong declines only started after the mid-1990s.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…By contrast, infected populations were even able to increase despite the presence of the fungus. Thus, our observation in the yellowbellied toad population Baumbach marl pit/Hergerhausen stone pit with high prevalence of Bd but population growth confirms that of Tobler et al (2012), who also concluded that observed negative effects of Bd on survival of individuals do not necessarily translate into negative effects at the population level. In yet another study, Canestrelli et al (2013) showed that Bd has been present in Apennine yellow-bellied toad populations Bombina pachypus at least since the late 1970s, but strong declines only started after the mid-1990s.…”
Section: Discussionsupporting
confidence: 84%
“…Mass mortalities or obvious signs of disease in individuals were not observed. Conversely, we could show that Bd-in fected populations can even increase in size under favorable habitat conditions, supporting the findings of Tobler et al (2012). Apart from longterm monitoring of yellow-bellied toad populations, we therefore call for maintenance measures that improve aquatic and terrestrial habitat conditions to keep or bring populations into a favorable conservation status.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Further mechanisms for coexistence may operate at the population level, such that even observable negative effects of Bd on the individual host do not automatically translate to negative effects at the population level [4,43]. In our case, both populations appeared relatively stable over the study period.…”
Section: (B) Population-level Patternsmentioning
confidence: 58%
“…In other species with enzootic infections, the absence of negative effects of Bd in population growth rates, survival, and recruitment may indicate the evolution of tolerance (Muths et al, 2011;Tobler et al, 2012). However, this is not the case for E. coqui because populations are still declining, Bd infection hinders frog survival and juveniles are more susceptible than adults .…”
mentioning
confidence: 99%